Terapi Dzikir Jahar Mengurangi Kecemasan Pada Ibu Pre Operasi Sectio Caecarea - Arisda Candra Satriyawati; Syaifurrahman Hidayat; Yulia Wardita; Nor Arifah (Wiraraja Medika : Jurnal Kesehatan, 2021)
Dhikr Jahar Therapy Reduces Anxiety in Pre-Operative Sectio Caesarea Mothers. Mothers often experience anxiety before cesarean section surgery. Non-pharmacological therapy with dhikr Jahar can be a complementary therapy option to reduce anxiety. This study aimed to explain the effect of dhikr therapy on reducing maternal anxiety levels before SC surgery. The research method uses Quasy Experiment with Pre-Post Test With Control Group Design. The respondents' determination was carried out by total sampling, namely pre-cesarean section surgery pregnant women in March-June 2019 at Garam Islamic Hospital, Kalianget (n=24). Statistical test using Paired T-Test, Wilcoxon Test, and Independent T-Test. The results of the Paired T-Test showed that there were differences in the level of anxiety of patients before SC before and before being given dhikr therapy in the intervention group (p = 0.000); there was an average decrease of 9.917. The Wilcoxon test results showed no difference (change) in the level of anxiety of patients before and before being given therapeutic communication in the control group the value (p = 0.636); the decrease that occurred was 0.83. In the Independent T-Test results, there was no difference in the level of anxiety before SC before and before being given treatment in the intervention group and the control group (p = 0.211). There is an effect of providing dhikr Jahar therapy to reduce maternal anxiety levels before SC surgery.